Characterization of a recombinant alkaline thermostable β-mannanase and its application in eco-friendly ramie degumming. (October 2017) - Wang, Yawei; Shu, Tong; Fan, Pei; Zhang, Huashan; Turunen, Ossi; Xiong, Hairong; Yu, Longjiang
Graphical abstract: Highlights: A novel gene ManB (GenBank:KJ806638 ) was synthesized following the amino acid sequence of mannanase 1BQC. A multi-copy secretive expression vector pAOhr was constructed to introduce the gene ManB into Pichia pastoris GS115. This recombinant alkaline thermostable mannanase ManB was characterized; Molecular docking showed that Tris molecule can bind to the enzyme active site. The additive mannanase ManB was helpful to remove the gums when combined with Bacillus sp. HG-28 for ramie degumming. Abstract: A codon optimized synthetic alkaline thermostable Thermobifida fusca β-mannanase ManB (KJ806638 ) was expressed in Pichia pastoris and used in ramie degumming. To improve the expression level, a multi-copy secretion expression vector pAOhr was constructed to introduce the ManB gene into Pichia pastoris GS115. The highest secretion yield was obtained from a transformant strain containing six copies of ManB gene. The size of ManB protein was 34 kDa in SDS-PAGE and the secreted protein was the main protein in the culture broth. The optimal activity region of ManB was at pH 7–9 and the enzyme was quite stable at pH 6–10. At pH 9, the specific activity of ManB was 493.8 IU/mg and the optimum temperature was 70–75 °C. ManB appeared to be inhibited by Tris buffer. Molecular docking showed that Tris molecule can bind to the enzyme active site. ManB exhibited high activity for locust bean gum, whereas it showed in practice no activity for CMC-Na. Ramie degumming was performed with combined treatment by ManB and Bacillus sp. HG-28 expressing pectinase and xylanase. The obtained results demonstrated that the combination treatment with additional mannanase enzyme was more efficient in removing the gums than the treatment merely by the bacterial strain.